The Relationship Between Peer Social Support and Academic Stress During the Covid-19 Pandemic for Students of the 3rd Semester of Psychology and Educational Sciences at Muhammadiyah University of Sidoarjo: Hubungan Antara Dukungan Sosial Teman Sebaya Dengan Stres Akademik Saat Pandemi Covid-19 Pada Mahasiswa Fakultas Psikologi dan Ilmu Pendidikan Semester 3 di Universitas Muhammadiyah Sidoarjo - Aulia Puspa Lestari Tari; Dwi Nastiti (Universitas Muhammadiyah Sidoarjo, 2022)
This research was conducted because of the phenomenon where early semester students experience academic stress. The purpose of this study was to determine the relationship between peer social support and academic stress in third semester students of the Faculty of Psychology and Educational Sciences, Muhammadiyah University of Sidoarjo. This study is a quantitative correlational research method. The research population was 569 students and 221 students were taken as a sample using the proportional sampling technique. The data collection method used 2 psychological scales, namely the Peer Social Support Scale and the Academic Stress Scale. The proposed hypothesis is that there is a negative relationship between peer social support. with academic stress. Data analysis with Pearson Product Moment Correlation. The result, r = -0.059, p = 0.191 (p > 0.05), which means the research hypothesis is rejected. This means that there is no relationship between peer social support and academic stress. Keywords: Peer Social Support, Academic Stress, Students.